2013
DOI: 10.3109/07420528.2013.817415
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Psychometric Properties of Contemporary Circadian Typology Measures

Abstract: The accurate measurement of circadian typology (CT) is critical because the construct has implications for a number of health disorders. In this review, we focus on the evidence to support the reliability and validity of the more commonly used CT scales: the Morningness-Eveningness Questionnaire (MEQ), reduced Morningness-Eveningness Questionnaire (rMEQ), the Composite Scale of Morningness (CSM), and the Preferences Scale (PS). In addition, we also consider the Munich ChronoType Questionnaire (MCTQ). In terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 86 publications
5
158
2
4
Order By: Relevance
“…Scores for the rMEQ range from 4 to 25; scores below 12 identify participants as evening-types and scores above 17 as morning-types. The psychometric properties of the rMEQ have been reviewed by Chelminski, Petros, Plaud, and Ferraro (2000) and by Di Milia, Adan, Natale, and Randler (2013), who concluded that this scale has high reliability and produces results that are highly correlated with those of the original MEQ and other commonly used scales. The Cronbach's α coefficient for the present study was 0.70.…”
Section: Methodsmentioning
confidence: 98%
“…Scores for the rMEQ range from 4 to 25; scores below 12 identify participants as evening-types and scores above 17 as morning-types. The psychometric properties of the rMEQ have been reviewed by Chelminski, Petros, Plaud, and Ferraro (2000) and by Di Milia, Adan, Natale, and Randler (2013), who concluded that this scale has high reliability and produces results that are highly correlated with those of the original MEQ and other commonly used scales. The Cronbach's α coefficient for the present study was 0.70.…”
Section: Methodsmentioning
confidence: 98%
“…In this study, we used a unidimensional construct of chronotype (as in most studies, see, e.g., Di Milia et al, 2013). However, recent findings proposed the multidimensional structure of chronotype with two or more dimensions, such as that morningness and eveningness are separate dimensions and not just the two poles of one continuum, as well as the aspect of amplitude/stability (e.g., Putilov, Donskaya, & Verevkin, 2015;Randler, Díaz-Morales, Rahafar, & Vollmer, 2016;Scherrer, Roberts, & Preckel, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chronotype is measured by different questionnaires developed for large scale survey (see Di Milia et al, 2013, for a review), and these questionnaires are medium to highly intercorrelated, suggesting that they measure a similar construct (Di Milia et al, 2013). Recently, Loureiro and GarciaMarques (2015) showed that the self-assessment item of the [Morningness-Eveningness-Questionnaire (MEQ)]/reduced MEQ (rMEQ) was highly correlated with the total score (>0.8 with rMEQ score).…”
Section: Why Study Chronotype Sleep and Personality?mentioning
confidence: 99%
“…Studies methodologies mainly differ in three ways: 47 studies have shown the reliability of its parameters in comparison to sleep logs, 48 actigraphy, 49 Morningness-Eveningness Questionnaire, 50,47 and Dim Light Melatonin Onset. 51 MCTQ considers the difference between bedtime and sleep onset time, and between rise time and wake up time.…”
Section: Methodological Heterogeneitymentioning
confidence: 99%